Foam‐based cleaning of surfaces contaminated with mixtures of oil and soot. Issue 3 (18th January 2022) - Schad, Tamara; Preisig, Natalie; Drenckhan, Wiebke; Stubenrauch, Cosima
Abstract: Liquid foams of intermediate stability have been shown to be very efficient in the cleaning of sensitive surfaces because of the synergy between imbibition and foam decay. While we quantified these mechanisms for contaminations with liquid oils in our previous work, we show here their extension to oils containing soot particles in an effort to simulate increasingly realistic contaminations. Using foams with a wide range of liquid fractions and with different stabilities, we show that the main cleaning mechanisms remain very similar, with the oil entraining the soot particles. However, we find much less efficient soot removal when the liquid channels of the foams are small enough to hinder efficient transport of the soot particles.